Comparable efficacy of adapalene 0.3% gel and tretinoin 0.05% cream as treatment for cutaneous photoaging - Bagatin, Edileia; Goncalves, Heitor de Sa; Sato, Mauricio; Costa Almeida, Luiz Mauricio; Miot, Helio Amante [UNESP] (John Libbey Eurotext Ltd, 2018)
Background: Adapalene has been previously evaluated as a treatment for actinic keratosis (AK) and solar lentigines and shown to improve signs of photoaging. Objectives: To evaluate whether adapalene 0.3% gel is non-inferior to tretinoin 0.05% cream as treatment for photoaged skin. Materials & Methods: An investigator-blinded, parallel-group comparison study was conducted in Brazil. Subjects were randomised in a 1:1 ratio to receive, once daily, adapalene 0.3% gel or tretinoin 0.05% cream. Subjects were evaluated at Weeks 1, 4, 8, 12, 16, 20 and 24, based on clinical signs of cutaneous photoaging, histopathological and digital morphometric findings, as well as safety and tolerability. Results: A comparison of clinical efficacy showed that both treatments did not differ significantly regarding clinical evaluation of the following criteria: global cutaneous photoaging, periorbital wrinkles, ephelides/melanosis, forehead wrinkles, and AK. Conclusion: Adapalene 0.3% gel showed non-inferior efficacy to tretinoin 0.05% cream as treatment for photoaged skin, with a similar safety profile. Adapalene 0.3% gel may therefore be considered a safe and effective option for the treatment of mild or moderate photoaging.
Keywords: adapalene; melanosis; photoaging; retinoid; tretinoin; wrinkles